2015
DOI: 10.1039/c5sm00964b
|View full text |Cite
|
Sign up to set email alerts
|

Reactive modeling of the initial stages of alkoxysilane polycondensation: effects of precursor molecule structure and solution composition

Abstract: Reactive molecular dynamics simulations are used to model polycondensation of alkoxysilanes in solution. Different precursor monomers are compared and steric effects on polycondensation kinetics are observed. The impact of the alcohol and water composition in solution are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…The smaller size of the hydroxyl groups in comparison with bulkier methoxy groups, as ligands on the silanes, enables easier accessibility for condensation with the surface. 23 Despite the accelerated kinetics of DTHS in comparison to DTMS, the formed monolayers show similar morphological characteristics, such as surface roughness, in-plane molecular area, tilt angle, and radius of gyration. This indicates that the alkoxylation of the substrate had little effect on the properties of the formed monolayer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The smaller size of the hydroxyl groups in comparison with bulkier methoxy groups, as ligands on the silanes, enables easier accessibility for condensation with the surface. 23 Despite the accelerated kinetics of DTHS in comparison to DTMS, the formed monolayers show similar morphological characteristics, such as surface roughness, in-plane molecular area, tilt angle, and radius of gyration. This indicates that the alkoxylation of the substrate had little effect on the properties of the formed monolayer.…”
Section: Discussionmentioning
confidence: 99%
“…The methoxy groups are bulkier and may hinder condensation. Past studies 18,23 have indicated that bulky alkoxysilane groups hinder hydrolysis and condensation. Another possible explanation for the enhanced kinetics of silanization is the lack of surface bound methoxysilane groups.…”
Section: Effects Of Hydrolyzation Of Silane Moleculementioning
confidence: 99%
See 1 more Smart Citation
“…Figure a illustrates the reaction procedure for QDs-SiO 2 -BNAs. In a typical reaction, QDs-SiO 2 particles were prepared according to a classical method. , BN nanoplates were surface-treated by silica encapsulation via a hydrolysis polycondensation reaction of tetramethoxysilane (TMOS) in ethanol. Subsequently, the QDs-SiO 2 -BNAs particles were prepared by simply mixing the QDs-SiO 2 particles with the BN-SiO 2 particles in ethanol solution in the presence of a slight amount of TMOS.…”
Section: Resultsmentioning
confidence: 99%
“…Silane alkoxy groups are first to be introduced onto polyolefin backbone by peroxideinitiated grafting of unsaturated silane, then transformed to siloxane ( Si O Si ) through catalytically hydrolytic condensation using water or moisture (Scheme 1). [5] Compared with the other two methods, silanecrosslinking has advantages of low capital investment and favorable properties of the processed materials. [6] In the case of polypropylene (PP), predominant macro-radical fragmentation during radiation and peroxide modification [7] means silane grafting and moisture crosslinking have a greater advantage in the production of crosslinked PP.…”
Section: Introductionmentioning
confidence: 99%